Trends in paediatric anaesthesia research publications and the impact of author sex, country of origin, topic, and external funding - Andy Jeon; Aine Sommerfield; Britta S. von Ungern-Sternberg (BJA Open)
Background: The current research landscape has become increasingly competitive with approximately 35% of submitted manuscripts accepted for publication by peer-review journals. It is known that studies with certain ‘favourable characteristics’ have an increased likelihood of acceptance for publication, such as prospective study design, multiple sites, and notable authors.We aimed to identify the characteristics of original research publications in paediatric anaesthesiology and the impact of these characteristics on citations. The characteristics selected were study design, topic choice, region of origin, sex of authors (as defined by first name), and presence of external funding. Methods: This bibliometric study reviewed all paediatric anaesthesiology original research articles published between 2012 and 2021 from five high-impact general anaesthesiology journals and from the subspecialty's top-ranking specialist journal, Pediatric Anaesthesia. Original research articles (n=1119) were independently assessed by two investigators for the following characteristics: primary research topic, study design, region of origin, number of sites involved, external funding status, sex of first and last author, and number of citations. Results: The principal findings in our study showed that highly cited articles in paediatric anaesthesiology were more likely to display publication characteristics such as prospective study design (66% vs 61%), multi-site (23%% vs 14%), and being externally funded (53% vs 46%). Conclusions: Our report highlights the need to consider consumer priorities for research, to encourage collaboration across institutions, and to generally improve access to funding for paediatric anaesthesiology research. In addition, the findings underline the already recognised need to reach better sex equality in academic paediatric anaesthesiology publications.